Seasonal variation lipid levels in the patients with dyslipidaemia - I V Radysh; A F Khisamutdinov; N D Kisliy (RUDN Journal of Medicine, 2009)
The article is devoted to study seasonal variation in blood lipid levels in the patients with dyslipidaemia IIa type. The 185 men with dyslipidaemia IIa and 173 healthy men volunteers aged 28 to 50 years were examined four times during the year: in winter (December-February), spring (March-May), summer (June-August) and autumn (September-November). Is established, that in the patients the shift acrophases of seasonal rhythms total cholesterol, LDL cholesterol, VLDL cholesterol and apoВ to the autumn, triglycerides - to winter was observed, and HDL cholesterol and apolipoproteinА-1 - to spring in comparison with healthy, that testifies to higher probability of development in them of atherosclerosis. Thus the maximal meanings index of atherogenesis and ratio of apoВ/apoА-1 were observed in the autumn and in the healthy - in winter. Is shown, that the peak C-reactive protein in the patients with dyslipidaemia was observed in the summer and in the healthy - in spring. Thus the shift acrophases of seasonal rhythms lipid spectrum in the patients with dyslipidaemia IIa type as to the autumn raises risk of development in them cardiovascular pathology